Radio Frequency Identification Upon Near Field Communication and Far Field Communication For Next Generation Wireless Network Infrastructures - Mushtaq, Gowher; Singh, Shashank; Tiwari, Neeraj Kumar; Rasheed, Seemab; pal, Yogesh; Srivastava, Kavita (Discoveries in Agriculture and Food Sciences, 2015)
The electromagnetic field that outlines the RFID antenna can be divided up into two portions – Near-field and Far-field. Near Field Communication (NFC) and Far-Field communication (FFC) both are the most emerging wireless short-range communication technologies, both are based on existing standards of the Radio Frequency Identification (RFID) network framework. In collaboration with NFC-efficient next generation smartphones it authorizes automatic application frameworks for contact less connections, in different exceptional utilities for future generation smartphone payment and over-the air ticketing. The principle aim of current study is to explain basic characteristics and benefits of the wireless short- range technologies like (RFID, NFC, and FFC) and analogy between them to classify modes of operation and to present various illustrations. NFC mechanism, applications and FFC with possible future or Next Generation scenarios will be analyzed. Finally, this study provides the fundamental security concerns; challenges and present conflicts will be investigated in order to achieve the efficiency in Next Generation Network Infrastructures.